Multi-objective optimization of the aerodynamic shape of a long-range guided rocket - Runduo, Cao; Xiaobing, Zhang (Structural and multidisciplinary optimization, 2018)
The parameter values associated with the optimal aerodynamic shape of a long-range guided rocket (LGR) are different from those of an unguided rocket because the shapes and design objectives are different. Here we establish a multi-objective optimization model of the aerodynamic shape of an LGR for the purpose. Moreover, a rapid aerodynamic calculation method is used, which is much more efficient than wind-tunnel tests or computational fluid dynamics (CFD). Previously, the aerodynamic shape of an unguided rocket would be optimized by identifying one parameter as a single objective and regarding the others as constraints. Here, we use version II of the non-dominated sorting genetic algorithm (NSGA-II) and the real-coding genetic algorithm (RGA) to solve this multi-objective optimization problem (MOP). The results obtained by the two algorithms show an improved lift/drag ratio of the LGR with optimal aerodynamic shape, better maneuverability, and acceptable stability. Furthermore, the optimum and original schemes are calculated using CFD, and the pressure contours show that the results are qualitatively correct. This method can be used to design the optimal aerodynamic shape of this type of rocket.